Wind loads characteristics of irregular shaped high-rise buildings. Issue 1 (January 2023) - Li, Yong-gui; Liu, Peng; Li, Yi; Yan, Jia-hui; Quan, Jia
Many irregular shaped high-rise buildings have been built for graceful demand of architecture or better amenity and ventilation in the world. In this study, a benchmark rectangular high-rise building model and six high-rise building models with various irregular shapes, including two T-shaped, two U-shaped, H-shaped and X-shaped, are tested in a boundary wind tunnel to investigate their wind loads characteristics. The coefficients, power spectral density and cross-correlation of base moments as well as local wind forces are analyzed and discussed in details. Based on the wind tunnel test results, it is founded that the effect of U-shape and H-shape on wind loads is negligible. The along-wind mean base moment coefficient of X-shaped model is increased by 10.0% in 90° wind direction. The wind force characteristics of T-shaped models are quite different from the benchmark model in many cases. The mean base moment coefficient of T-shaped 2 model is reduced by 18.6% in 0° wind direction. Larger mean lift forces and torques of T-shaped models are appeared and there is a certain correlation between along-wind and across-wind local wind forces in 90° wind direction.